The validity evaluation of different 16srRNA gene primers for helicobacter detection urgently requesting to design new specific primers - Shaymaa Abdelmalek; Karim Shokry; Wafy Hamed; Mohammed Abdelnaser; Ashraf Aboubakr; Sameh Abou Elenin; Mohamed Ali; Mohamed Mostafa; Mahmoud Abou-Okada (Scientific Reports, 2022)
Abstract Molecular diagnosis of helicobacters by PCR is simpler, more accurate, and feasible compared to other diagnostic methods. Validity and accuracy are highly dependent on the PCR primer design, diffusion time, and mutation rate of helicobacters. This study aimed to design 16srRNA -specific primers for Helicobacter spp. and H. pylori. Application of comparative statistical analysis of the diagnostic utility of the most available 16srRNA genus-specific primers. The new primers were designed using bioinformatics tools (MAFFT MSA and Gblocks command line). A comparative study was applied on nine genus-specific 16srRNA primers in comparison to the ConsH using in silico and laboratory evaluation. The results demonstrated that the best specificity and sensitivity of the primers designed for this study compared to other primers. The comparative study revealed that the heminested outer/inner primers were the worst. Although H276, 16srRNA(a), HeliS/Heli-nest, and Hcom had acceptable diagnostic utility, false positive and false negative results were obtained. Specificity testing on clinical samples indicated a surprising result; that H. pylori was not the sole enemy that we were looking for, but the Non-Helicobacter pylori Helicobacters should be considered as a real risk prognostic for gastric diseases, consequently, a specific diagnosis and treatment should be developed. This study concluded that our designed primers were the most specific and sensitive in comparison with other primers. In addition, in silico evaluation is not accurate enough for primer assessment and that the laboratory evaluation is mandatory.